Kesetaraan Gender dalam Hukum Islam: Implikasi Wanita Karir di Era Digital - Rimbawan, Israh Dwi; Sanallah, Muh.; A, Ardiwansa; K, Kurniati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Gender equality in Islamic law plays an important role in supporting women’s participation in the professional world, especially in the digital era which offers many new opportunities. Even though the principle of equal rights and obligations is recognized, women often face challenges in the form of their dual roles as professionals and housekeepers, as well as obstacles related to social standards. Gender equality means that men and women have the same rights and responsibilities in the work environment. Islamic law, which regulates all aspects of life, strives to remain alive along with the times. This research is qualitative in nature and collects data through literature study and descriptive approaches. The collected data was then analyzed using a gender analysis approach. The results of this research show that Islamic law supports gender equality and recognizes women’s rights and responsibilities, including in their careers. In the digital era, opportunities for women to develop careers are increasingly open. Technology provides space for women to have a career from anywhere. Career women are not prohibited in Islam, as long as their professional activities are in accordance with the provisions of the Shari’a and Islamic principles. Islamic law allows women to play an active role in society without ignoring religious values.